Acute kidney injury and outcomes in hospitalized children with autoimmune rheumatic disease - Chien-Hung Lin; Wen-Sheng Liu; Chuan Wan; Hsin-Hui Wang (Italian Journal of Pediatrics)
Abstract Background Autoimmune rheumatic diseases (ARDs) in children can negatively impact renal function, potentially leading to acute kidney injury (AKI). This study compares the prevalence of AKI and other adverse in-hospital outcomes among hospitalized children with ARDs. Methods A retrospective analysis was conducted using the United States Nationwide Inpatient Sample (NIS) database from 2005 to 2020. The study included children aged 1–17 years with ARDs, categorized into inflammatory arthritis, ANCA-associated vasculitis, systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and other connective tissue diseases. Logistic regression assessed associations between ARD types and outcomes, including AKI, dialysis, and major adverse events. Results Among 13,891 children with ARDs, 8.2% developed AKI and 1.3% required dialysis. Compared to inflammatory arthritis, ANCA-associated vasculitis significantly increased the risk of AKI (aOR = 11.20, 95% CI: 8.08–15.51) and dialysis (aOR = 40.60, 95% CI: 13.54-121.71). SLE also elevated risks of AKI (aOR = 4.16, 95% CI: 3.20–5.40) and dialysis (aOR = 11.34, 95% CI: 4.15–31.01). Children with SSc had increased risks of infection/pneumonia (aOR = 2.51, 95% CI: 1.84–3.41) and sepsis (aOR = 2.13, 95% CI: 1.26–3.58). Conclusions Children with ARDs, especially those with ANCA-associated vasculitis and SLE, face elevated risks of AKI and dialysis. These findings underscore the importance of vigilant monitoring and tailored management in this population.